Legal Implications of Violating Healthcare Service Standards for BPJS Patients: A Juridical Study - Nugroho, Enggar Adi; Anggraeni, Happy Yulia (Research Horizon, 2025)
Legal protection for Social Security Administration Agency (Badan Penyelenggaran Jaminan Sosial/BPJS) participants in cases of violations of healthcare service standards remains a critical issue. This study purpose to analyze the effectiveness of civil, criminal, and administrative legal mechanisms in providing repressive legal protection for Social Security Administration Agency patients in cases of medical negligence. Using a normative juridical approach, the research examines three civil court decisions from 2019–2023 that explicitly involve BPJS patients and complements this with an analysis of relevant criminal and administrative regulations, including the role of the Indonesian Medical Disciplinary Honor Council. The study reviews the Civil Code, the Criminal Code, Law Number 17 of 2023 on Health, and Law Number 29 of 2004 on Medical Practice. The results show that all three lawsuits filed by BPJS patients were rejected or declared inadmissible due to procedural defects, error in persona, or the high burden of proof for medical negligence. Criminal liability under Articles 359–360 of the Criminal Code is applied selectively, while MKDKI sanctions function predominantly in a preventive rather than corrective manner. It is concluded that legal protection for BPJS participants remains largely normative and ineffective in practice, requiring reforms to evidentiary standards and accountability mechanisms.